Habits and Patterns Of Watching Arabic Satellite Dedicated Children's Channels Afield Study On A Sample Of Basic Education Students In Lattakia City (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed at identification habits and patterns of watching Arabic satellite dedicated children's channels, and it also aimed at studying differences to (age, gender). This research was applied to a sample of (648) students at basic education schools in Lattakia city for the year (2015-2016). This research used descriptive analytical methodology,it depended on questionnaire to collect data. To be sure of questionnaire validity it presented to (7) arbitrators of Tishreen university staff, and to be sure of reliability it was applied to survey of (50) students by test-retest reliability, it reached (0,80). Results showed that basic education students of research sample watching stellate dedicated children' channels in high percentage, and children preferred watching (Spacetoon Arabic) channel. They preferred watching Cartoon. The most significant reasons of watching were having fun and entertain. Most of children watch these programs with their brothers. They watch these channels all the week for one to two hours daily. There were no statistically differences in order to gender and there were no statistically differences in order to age. The research offered many suggestions, most important were: taking care of children programs content in dedicated children's channels.